(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The notion of semidetached Sheffer stroke UP-algebras is introduced, and their properties are investigated. Several conditions for a semidetached structure in Sheffer stroke UP-algebras to be a semidetached SUP-subalgebra are provided. The concepts of (,q_k)-fuzzy SUP-subalgebra, k-left (k-right) (q_k, q_k)-fuzzy SUP-subalgebra, (q_k, q_k)-fuzzy SUP-subalgebra and (q_k, q_k)-fuzzy SUP-subalgebra are introduced, and relative relations and properties are discussed.